2018
DOI: 10.1057/s11231-018-9137-6
|View full text |Cite
|
Sign up to set email alerts
|

Authority, Psychotherapy and the Authority of the Therapist in the Religious Haredi Community

Abstract: This article considers the meaning and significance of authority, and its relevance to the transference process, within the framework of psychotherapy in the orthodox Jewish (Haredi) community in Israel. In this community, deeply-rooted habits of obedience to the commandments of the Torah and the authority of the Rabbi are integral to maintaining an orthodox way of life. Clinical vignettes with Haredi patients are presented to illustrate the complexities that arise when both patient and therapist belong to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Analysis of health care use in this trial showed fewer cardiac imaging tests and lower overall 45-day health care use in patients randomized to the decision aid. 7,8…”
Section: Choosing the Right Pathway With Patient-centric Algorithms F...mentioning
confidence: 99%
“…Analysis of health care use in this trial showed fewer cardiac imaging tests and lower overall 45-day health care use in patients randomized to the decision aid. 7,8…”
Section: Choosing the Right Pathway With Patient-centric Algorithms F...mentioning
confidence: 99%
“…The leading rabbinic authority prohibits psychiatric patients from consulting heretic or atheist psychologists or psychiatrists, fearing a clash with religious-cultural norms (Rube and Kibel, 2004). The relationship hierarchy with traditional Jewish law (Halacha) and the rabbi is elevated above therapy Band-Winterstein, 2013, 2017), and introduces continuous tensions and conflicts within the therapeutic dynamic, such as conflicts of loyalties, the forbidden and the permitted, or between right and wrong (Hess, 2018). When people in the UO community face difficulties in their lives, in their moods, in their behavior, they will choose to uphold the commandments even more stringently to raise their level of spirituality in order to improve their personal-emotional state.…”
Section: Ultra-orthodox Jews and Psychotherapymentioning
confidence: 99%
“…The leading rabbinic authority prohibits psychiatric patients from consulting heretic or atheist psychologists or psychiatrists, fearing a clash with religious-cultural norms ( Rube and Kibel, 2004 ). The relationship hierarchy with traditional Jewish law (Halacha) and the rabbi is elevated above therapy ( Freund and Band-Winterstein, 2013 , 2017 ), and introduces continuous tensions and conflicts within the therapeutic dynamic, such as conflicts of loyalties, the forbidden and the permitted, or between right and wrong ( Hess, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is now greater acceptance of psychotherapy and outside help, especially for children at risk [ 27 ], studies show that the intercultural gap still impacts the ultra-Orthodox encounter with psychotherapy and creates significant conflicts [ 28 ]. For example, ultra-Orthodox clients may experience a conflict between dealing with difficulties privately and autonomously within the community and seeking help from external sources [ 11 ], difficulty opening up about issues that are not culturally acceptable [ 29 ], expecting practical solutions that are limited to what is allowed and forbidden according to culture and religion [ 30 ], and fear of stigma that may lead to negative consequences for future matchmaking of the individual and other family members, the ability to get a job in the community, social ties, and integration in educational institutions [ 31 , 32 ]. In child therapy, these difficulties can be intensified for the ultra-Orthodox client’s parents, who feel a sense of responsibility for the child’s religious and spiritual education [ 33 ].…”
Section: Introductionmentioning
confidence: 99%